Corporate criminal liability and compliance in Argentina - Yacobucci, Guillermo J. (2025)
This article aims to give a general overview of Compliance Programs in Argentina criminal law within the framework established by the Corporate Criminal Liability Law n° 27.401 and the Criminal Code. The reform introduced, for the first time in Argentina, the criminal liability of legal entities. The paper shows clearly the close relationship between the compliance and the corporate criminal liability in Argentina´s law. The existence of an effective compliance program protects, under certain conditions, against corporate criminal liability for some wrongdoing or misconduct of its directors or employees. Therefore, building a solid foundation of compliance increases the chances of a corporation avoiding criminal liability for a crime; even to exemption of criminal sanction.